HARDY-ROGERS TYPE MAPPINGS ON DISLOCATED QUASI METRIC SPACES - Padcharoen, A.; Gopal, D.; Akkasriworn, N. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2017)
In this paper, We prove some common fixed point results for two $α$-dominated mappings satisfying Hardy-Rogers Type on a closed ball of left (right) $K$-sequentially complete dislocated quasi-metric space and give some example for support our result.